Moving to become healthier? - Edvard Johansson; Petri Böckerman; Seppo Koskinen (Elsevier, 2020)
This paper examines individuals' health and whether it improves when individuals move from a region with poorer health on average to a region with better health on average. We used data from Finland, which is a country with large regional differences in health behaviours and outcomes. We found no evidence that moving from a less healthy region to a healthier region would have any significant effect on the health of individuals who move compared with the health of other individuals. We also examined the potential heterogeneity in the analysed relationships. We found evidence of a relationship between moving itself and health improvements, but this generally true only for our subsample of individuals who had only average or poorer health before moving.